1993
DOI: 10.1002/jcb.240531005
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen biomarkers related to smoking and upper aerodigestive tract cancer

Abstract: Smoking is the major cause of upper aerodigestive tract cancers. Among the many constituents of tobacco smoke, polynuclear aromatic hydrocarbons and tobacco-specific nitrosamines are strongly implicated as causative factors for these cancers. The probability that these compounds will induce cancer in a given individual will depend on that person's ability to metabolically activate or detoxify them. Chronic production of DNA damage by these metabolically activated carcinogens is consistent with current concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…These factors together may be an important reason why codon 249 of p53 gene is a mutational hotspot in hepatocellular carcinoma. Cigarette smoke is the major cause of lung cancer, and polycyclic aromatic hydrocarbons generated in cigarette smoke have been suggested as being responsible for the initiation and development of lung cancer (39). Previously, we have found that polycyclic aromatic hydrocarbons including BPDE preferentially bind at mutational hotspots in smoke-related lung cancer, such as codons 157, 158, 245, 248, 273, and 282, but not codon 249 (16,40).…”
Section: Discussionmentioning
confidence: 99%
“…These factors together may be an important reason why codon 249 of p53 gene is a mutational hotspot in hepatocellular carcinoma. Cigarette smoke is the major cause of lung cancer, and polycyclic aromatic hydrocarbons generated in cigarette smoke have been suggested as being responsible for the initiation and development of lung cancer (39). Previously, we have found that polycyclic aromatic hydrocarbons including BPDE preferentially bind at mutational hotspots in smoke-related lung cancer, such as codons 157, 158, 245, 248, 273, and 282, but not codon 249 (16,40).…”
Section: Discussionmentioning
confidence: 99%
“…Discussion CS is the major cause of lung cancer deaths, and 90% of all lung cancers in the United States are CS-related (28,29). CS contains Ͼ4,000 compounds, many of which, including PAHs, Nnitrosamines, aromatic amines, and metals, are not only mutagenic but also well established carcinogens in animal models (8,29,30). Therefore, it is reasonable to assume that these compounds contribute to CS-related lung carcinogenesis in humans.…”
Section: Acr-dg Adducts Induce G-to-t Transversion Mutations In Humanmentioning
confidence: 99%
“…Relating dosimetry to the mutational spectra of histologic typespeci c cancers may provide clues to why certain cancer types develop in particular anatomic locations while others do not (Weston and Bowman 1991). In addition, dosimetry could aid in the development of chemopreventive agents which target speci c lung cells and inhibit the progression stages of carcinogenesis (Wattenberg 1992;Hecht et al 1993Hecht et al , 1994. Muller et al (1990) presented a model of CSP deposition in the human respiratory tract that approximated the hygroscopic nature of CSP as being similar to that of NaCl.…”
Section: Benzo[a]pyrene and Csp Depositionmentioning
confidence: 99%